Seniman Pewaris Nabi Perspektif Kesenian Profetik dalam Seni Pertunjukan Teater Aliran Realis - Wawan Kardiyanto (Lakon Jurnal Pengkajian & Penciptaan Wayang, 2019)
Prophetic art is art that contains prophetic and divine values synergizing universal values of humanity and divinity, namely truth, goodness, justice and beauty. Religious and social communities try to find ontological, epistemological and axiological values of prophetic arts. The prophetic value that was built by theater performance of realist script Pertja became the main study that presented awareness for the audience. It says that in order to live happily in the afterlife, then carry out God's commands and stay away from His prohibitions; do not make God angry so that life is not miserable as experienced by the characters of Rosa, Pupu, Selasih in Pertja performance. The values of truth, goodness and beauty that are carried by prophetic art can be seen in the content conveyed in Pertja's work which is able to bring darkness into light, namely truth for the sake of Allah SWT.Keywords: Art, prophetic, theater, Pertja script